Gestation-dependent increase in cervicovaginal pro-inflammatory cytokines and cervical extracellular matrix proteins is associated with spontaneous preterm delivery within 2 weeks of index assessment in South African women - Amabebe, Emmanuel; Ikumi, Nadia; Oosthuizen, Ally; Soma-Pillay, Priya; Matjila, Mushi; Anumba, Dilly O. C. (Frontiers in Immunology, 2024)
Introduction Inflammation-induced remodelling of gestational tissues that underpins spontaneous preterm birth (sPTB, delivery < 37 weeks’ gestation) may vary by race and context. To explore relationships between markers of these pathological processes, we (a) characterised the cervicovaginal fluid (CVF) cytokine profiles of pregnant South African women at risk of PTB; (b) determined CVF matrix-metalloproteinase-9 (MMP-9) and its regulator tissue inhibitor of metalloproteinase-1 (TIMP-1); and (c) explored the predictive potential of these markers for sPTB. Method of study The concentrations of 10 inflammatory cytokines and MMP-9 and TIMP-1 were determined by ELISA in CVF samples from 47 non-labouring women at high risk of PTB. We studied CVF sampled at three gestational time points (GTPs): GTP1 (20–22 weeks, n = 37), GTP2 (26–28 weeks, n = 40), and GTP3 (34–36 weeks, n = 29) and analysed for changes in protein concentrations and predictive capacities (area under the ROC curve (AUC) and 95% confidence interval (CI)) for sPTB. Results There were 11 (GTP1), 13 (GTP2), and 6 (GTP3) women who delivered preterm within 85.3 ± 25.9, 51.3 ± 15.3, and 11.8 ± 7.5 (mean ± SD) days after assessment, respectively. At GTP1, IL-8 was higher (4-fold, p = 0.02), whereas GM-CSF was lower ( 1.4-fold, p = 0.03) in the preterm compared with term women with an average AUC = 0.73. At GTP2, IL-1β (18-fold, p < 0.0001), IL-8 (4-fold, p = 0.03), MMP-9 (17-fold, p = 0.0007), MMP-9/TIMP-1 ratio (9-fold, p = 0.004), and MMP-9/GM-CSF ratio (87-fold, p = 0.005) were higher in preterm compared with term women with an average AUC = 0.80. By contrast, IL-10 was associated with term delivery with an AUC (95% CI) = 0.75 (0.55–0.90). At GTP3, IL-1β (58-fold, p = 0.0003), IL-8 (12-fold, p = 0.002), MMP-9 (296-fold, p = 0.03), and TIMP-1 (35-fold, p = 0.01) were higher in preterm compared with term women with an average AUC = 0.85. Elevated IL-1β was associated with delivery within 14 days of assessment with AUC = 0.85 (0.67–0.96). Overall, elevated MMP-9 at GTP3 had the highest (13.3) positive likelihood ratio for distinguishing women at risk of sPTB. Lastly, a positive correlation between MMP-9 and TIMP-1 at all GTPs (ρ ≥ 0.61, p < 0.01) for women delivering at term was only observed at GTP1 for those who delivered preterm (ρ = 0.70, p < 0.03). Conclusions In this cohort, sPTB is associated with gestation-dependent increase in pro-inflammatory cytokines, decreased IL-10 and GM-CSF, and dysregulated MMP-9-TIMP-1 interaction. Levels of cytokine (especially IL-1β) and ECM remodelling proteins rise significantly in the final 2 weeks before the onset of labour when sPTB is imminent. The signalling mechanisms for these ECM remodelling observations remain to be elucidated.